Valproic Acid and Lithium Meditate Anti‐Inflammatory Effects by Differentially Modulating Dendritic Cell Differentiation and Function. Issue 5 (10th November 2016) - Leu, Sy‐Jye; Yang, Yi‐Yuan; Liu, Hsing‐Cheng; Cheng, Chieh‐Yu; Wu, Yu‐Chen; Huang, Ming‐Chyi; Lee, Yuen‐Lun; Chen, Chi‐Ching; Shen, Winston W.; Liu, Ko‐Jiunn
Abstract : Valproic acid (VPA), with inhibition activity mainly toward histone deacetylase (HDAC) and Glycogen Synthase Kinase (GSK)‐3, and lithium, with inhibition activity mainly toward GSK‐3, are both prescribed in clinical as mood‐stabilizers and anticonvulsants for the control of bipolar disorder. This study aims to compare the immuno‐modulation activities of VPA and lithium, especially on the differentiation and functions of dendritic cells (DC). Our data show that treatment with VPA or lithium effectively alleviated the severity of collagen‐induced arthritis triggered by LPS in mice. Both agents reduced the serum level of IL‐6 and IL‐10 after LPS challenge in mice. VPA and lithium both induce significant down‐regulation of group I CD1 expression and secretion of IL‐6 during differentiation of human monocyte‐derived immature DC, while they differ in the induction of CD83 and CD86 expression, secretion of IL‐8, IL‐10, and TNF‐α. Upon stimulation of immature DC with LPS, VPA, and lithium both reduced the secretion of IL‐6 and TNF‐α. However, only lithium significantly increased the production of IL‐10, while VPA increased the production of IL‐8 but substantially reduce the secretion of IL‐10 and IL‐23. Treatment with VPA resulted in a reduced capacity of LPS‐stimulated DC to promote the differentiation of T helper 17 cells that are critical in the promotion of inflammatory responses. Taken together, our results suggest that VPA and lithium may differentially modulate inflammation through regulating the capacity of DC to mediate distinct T cell responses, and they may provide a complementary immunomodulatory effects for the treatment of inflammation‐related diseases. J. Cell. Physiol. 232: 1176–1186, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Upon stimulation of immature DC with LPS, VPA, and lithium both reduced the secretion of IL‐6 and TNF‐α. However, only lithium significantly increased the production of IL‐10, while VPA increased the production of IL‐8 but substantially reduce the secretion of IL‐10 and IL‐23. Treatment with VPA resulted in a reduced capacity of LPS‐stimulated DC to promote the differentiation of T helper 17 cells. VPA and lithium may differentially modulate inflammation through regulating the capacity of DC to mediate distinct T cell responses, and they may provide a complementary immunomodulatory effects for the treatment of inflammation‐related diseases.